Taxing banks: An evaluation of the German bank levy - Claudia M. Buch; Björn Hilberg; Lena Tonzer (Deutsche Bundesbank, 2014)
Bank distress can have severe negative consequences for the stability of the financial system, the real economy, and for public finances. Regimes for the restructuring and resolution of banks, financed by bank levies and fiscal backstops, seek to reduce these costs. Bank levies attempt to internalize systemic risk and to increase the costs of leverage. This paper evaluates the effects of the German bank levy implemented in 2011 as part of the German Bank Restructuring Act. Our analysis offers three main insights. First, revenues raised through the bank levy are lower than expected, because of low tax rates and high thresholds for tax exemptions. Second, the bulk of the payments were contributed by large commercial banks and by the central institutions of savings banks and credit unions. Third, for the banks affected by the levy, we find evidence for a reduction in lending and higher deposit rates.
Keywords: G21; G28; C21; 330; bank levy; bank lending; interest rates; German banks